Combining visible light catalysis and transfer hydrogenation for in situ efficient and selective semihydrogenation of alkynes under ambient conditions. Issue 9 (23rd November 2015) - Zhong, Jian-Ji; Liu, Qiang; Wu, Cheng-Juan; Meng, Qing-Yuan; Gao, Xue-Wang; Li, Zhi-Jun; Chen, Bin; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : By combining visible light catalysis and transfer hydrogenation, we are able to convert a series of alkynes to their corresponding alkenes in high chemical yields. Abstract : By combining visible light catalysis and transfer hydrogenation, we are able to convert a series of alkynes to their corresponding alkenes in high chemical yields. Then the visible light catalytic transfer hydrogenation reaction can couple photoisomerization to produce E -alkenes or Z -alkenes exclusively depending on the aryl or alkyl substituted alkynes.